2014
DOI: 10.1508/cytologia.79.215
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Industry Wastewater–Induced Genotoxicity in Mice Using the Bone Marrow Micronucleus and Sperm Morphology Assays

Abstract: SummaryThe tobacco industry is one of the biggest industries in the world. Large quantities of wastewater are generated during processing and cigarette-making which may be toxic to the environment and public health. In this study, the potential genotoxicity of tobacco wastewater was evaluated using mice bone marrow micronucleus and sperm morphology assays. The wastewater was considered at concentrations of 1, 5, 10, 25, 50, 75 and 100% (v/v, wastewater/distilled water). There was concentration-dependent induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Current techniques of manufacturing tobacco products are quite different from ancient methods as it includes many additive chemicals to provide better taste (Gönen, 2005). However, large quantities of wastewater are generated in tobacco industries during processing and cigarette-making which may be toxic to the environment and public health (Alabi et al, 2014). Tobacco manufacturing is two-step process where first step is the production of tobacco that does not contribute to contaminate the water.…”
Section: Introductionmentioning
confidence: 99%
“…Current techniques of manufacturing tobacco products are quite different from ancient methods as it includes many additive chemicals to provide better taste (Gönen, 2005). However, large quantities of wastewater are generated in tobacco industries during processing and cigarette-making which may be toxic to the environment and public health (Alabi et al, 2014). Tobacco manufacturing is two-step process where first step is the production of tobacco that does not contribute to contaminate the water.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the number of viable sperm cells in an organism may be an additional factor in male infertility. 42 …”
Section: Discussionmentioning
confidence: 99%
“…The result was pooled for all the mice/group and then reported as mean sperm count/mL of suspension. 42 …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, many of these industrial effluents are discharged untreated into water bodies, partly because of weak regulations, thereby contaminating the receiving surface and ground waters. Reports have shown that effluents from pharmaceutical industry (Bakare et al, 2009;, hospitals (Iyekhoetin et al, 2011), universities (Alabi et al, 2012), tobacco industry (Alabi et al, 2014), automobile workshops (Alabi et al, 2016) and cocoa industry (Alabi et al, 2017) contained heavy metals and other chemical constituents in high concentrations capable of contaminating drinking water sources and lead to public health detrimental effects.…”
Section: Industrial Effluentsmentioning
confidence: 99%